Effects of Radix Adenophorae and Cyclosporine A on an OVA-Induced Murine Model of Asthma by Suppressing to T Cells Activity, Eosinophilia, and Bronchial Hyperresponsiveness - Seong-Soo Roh; Seung-Hyung Kim; Young-Cheol Lee; Young-Bae Seo (Hindawi Limited, 2008)
The present study is performed to investigate the inhibitory effects of Radix Adenophorae extract (RAE) on ovalbumin-induced asthma murine model. To study the anti-inflammatory and antiasthmatic effects of RAE, we examined the development of pulmonary eosinophilic inflammation and inhibitory effects of T cells in murine by RAE and cyclosporine A (CsA). We examined determination of airway hyperresponsiveness, flow cytometric analysis (FACS), enzyme-linked immunosorbent assay (ELISA), quantitative real time (PCR), hematoxylin-eosin staining, and Masson trichrome staining in lung tissue, lung weight, total cells, and eosinophil numbers in lung tissue. We demonstrated how RAE suppressed development on inflammation and decreased airway damage.